(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The need to determine the effectiveness of using technology in the students’ performances is very timely to be able to give needed assistance and training. There is a need to equip learners with the necessary skills and experiences that will enable them to become contributing members of the global community. Technology in education helps students attain quality education, which in return helps them pursue their life goals and future careers. Technology in education can be a tool for every student’s success. The researchers used a correlational quantitative research method in investigating and collecting information about the effectiveness of using technology on students’ academic performance. To get the intended data for specific questions stated in the statement of the problem, the researcher used purposive sampling. Lastly, the researcher questionnaire was utilised to determine the general effectiveness of using technology towards the academic performances of the students. Based on the analysis, it was discovered that most devices used in online classes are cell phones. The researchers also discovered the problems encountered by the respondents, such as experiencing poor internet connection. This is found to be the leading problem or challenge for these students. Concerns in LMS in times of answering activities, examinations, and study cause interruptions. The assessment shows a significant relationship between using technology and academic performance. On the other hand, the researchers provided the following recommendations: 1. the researcher recommends students continue to use technology in their studies because it allows them to improve their cognitive skills, which in turn helps them improve their academic performance; 2. students must keep using cell phones in their online learning; 3. smartphone is carried on the person so it is accessible anywhere and at any time. This makes accessing learning content easy, regardless of the location or the time of day. It allows students to access the tools that expand their learning without interruption. Learning is available, literally at their fingertips.